INFLUENCE OF LEGAL AWARENESS EDUCATION PASSES CROSS ON TUDENTS AGAINST TRAFFIC ACCIDENTS IN BOGOR CITY POLICE BASED ON LAW NO. 22 OF 2009 ON TRAFFIC AND ROAD TRANSPORTATION - Devyra Pravitasari; Ani Yumarni; Inayatullah Abd. Hasym (JURNAL HUKUM DE'RECHTSSTAAT, 2017)
Traffic is education through direct practice. In contrast to education in schools or upgrading which only emphasizes the planting norm verbally. Many students in the city of Bogor who do not know the ethics in traffic. If this continues, the number of accidents will continue to rise. Thus indispensable integrating traffic ethics education into the school curriculum so that the students know and apply traffic ethics. Provision of material ethics not only ethics in everyday life, but also traffic ethics material delivery is also very important for safety in road traffic. The fate of our nation is in the hands of young generation, thus expected our nation better and comply with the law. Legal research is a process of finding the rule of law, principles of law, as well as legal doctrine in order to address the legal issues at hand. The conclusion from this study is Increased legal awareness of traffic to the students of Bogor City through education traffic based on Law Number 22 Year 2009 regarding Traffic and Road Transportation conducted Unit Dikyasa Police Bogor City is to run learning programs traffic theoretically about safety traffic. The program is carried out with the planting of knowledge about traffic safety in the classroom, giving a brief training, simulation, and workshops, then students can practice it when he left and came home from school. In addition Dikyasa Unit Bogor City Police to raise awareness of traffic laws against students Bogor implement: a) Socialization of Law Number 22 Year 2009 regarding Traffic and Road Transportation; b) traffic education to educational institutions; c) Police go to campus; d) safety program ridding; e) Saka Bhayangkara traffic, and f) Installation of banners orderly traffic in the streets, government agencies, and educational institutions. of traffic education programs on legal awareness of high school students in the city of Bogor is a reduction in the level of traffic offenses committed by students as well as the declining number of traffic accidents among students, as well as increased compliance and understanding of students about the signs, markings and traffic ethics.